2006
DOI: 10.1111/j.1365-2443.2006.00943.x
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte growth‐dependent progression of maternal imprinting in mice

Abstract: In mammals, some genes categorized as imprinted genes are exclusively expressed either from maternal or paternal allele. This parental-origin-specific gene expression is regulated by epigenetic modification of DNA methylation in differentially methylated region (DMR), which is independently imposed during oogenesis and spermatogenesis. It is known that methylation of DMR in the female germ line is established during oocyte growth phase. However, the cause of the progression of methylation on DMR, due to either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
201
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(215 citation statements)
references
References 36 publications
10
201
2
2
Order By: Relevance
“…The report suggested that imprinting anomalies can affect more than one imprinted locus and may alter the clinical presentation of imprinted disease. The results from juvenile mice oocytes showed that progression of DMR methylation for each imprinted gene examined, including Zac1/Lot1 and Lit1, was dependent on oocyte growth or size (Hiura et al, 2006). Similarly, it was found that DNA methylation of PLAGL1/LOT1/ZAC1 and HYMAI is established during the growth phase of oogenesis, which coincides with monoallelic expression from the ICR or the DMR (Arima and Wake, 2006).…”
Section: Imprinting and Chromosomal Duplicationmentioning
confidence: 87%
“…The report suggested that imprinting anomalies can affect more than one imprinted locus and may alter the clinical presentation of imprinted disease. The results from juvenile mice oocytes showed that progression of DMR methylation for each imprinted gene examined, including Zac1/Lot1 and Lit1, was dependent on oocyte growth or size (Hiura et al, 2006). Similarly, it was found that DNA methylation of PLAGL1/LOT1/ZAC1 and HYMAI is established during the growth phase of oogenesis, which coincides with monoallelic expression from the ICR or the DMR (Arima and Wake, 2006).…”
Section: Imprinting and Chromosomal Duplicationmentioning
confidence: 87%
“…Maternal-specific de novo DNA methylation occurs in postnatal growing oocytes, [56][57][58] and methylation acquisition is related to oocyte size. 57,58 DNA methyltransferases A (DNMT3A) and its cofactor DNA methyltransferases L (DNMT3L) are required to establish DNA methylation in growing oocytes. 59 Maternalspecific de novo DNA methylation likely contributes to gene regulation in the oocyte and marks specific genes for activity in the embryo, as in the case of imprinted genes.…”
Section: Hdac2 Regulates Global Dna Methylation and Genomic Imprintinmentioning
confidence: 99%
“…It is commonly accepted that reprogramming of oocyte chromatin involves a set of epigenetic modifications. Examination of the pattern of DNA methylation in specific sequences indeed proved that genomic imprinting, a process contrib-uting to reprogramming, takes place during oocyte growth (OBATA & KONO 2002;HIURA et al 2006). Other study reported that methylation and acetylation of histones as well as the level of global DNA methylation changes during oocyte growth in mice (KAGEYAMA et al 2007).…”
mentioning
confidence: 96%